The frequency of diseases and awareness of the patients about medicines at a faculty of dentistry - Yasin Yasa; Busra Nur Gokkurt Yilmaz; Tunahan Tuna; Furkan Ozbey; Dilek Coban; Zerrin Unal Erzurumlu; Elif Sadik (Medicine Science)
The presence of systemic diseases and the medications used by patients presenting to the dentist have a significant impact on oral health and the dental treatment plan. The aim of this study was to determine the prevalence of systemic diseases in patients attending the Faculty of Dentistry and to investigate the awareness of the medications used by patients. A total of 635 patients with systemic diseases who applied to the Ordu University Faculty of Dentistry, Department of Dentomaxillofacial Radiology between November 2021 and May 2022 were included in the study. In addition to demographic information, a questionnaire consisting of 2 questions was applied to patients with at least one systemic disease. 63.1% of the patients were female and 36.9% were male. The most common systemic diseases were hypertension (41.2%), diabetes (22.4%), thyroid disorders (11.3%) and cardiac diseases (8.9%) respectively. According to the patients' answers, 45.1% knew their systemic disease and the medicine they were taking, 53.7% knew their systemic disease but did not know the medicine they were taking, and 1.2% did not know their systemic disease but knew the medicine they were taking. It is important for individuals who apply to the dentist to have knowledge and awareness about their systemic diseases and the medicine used, in order to prevent possible complications related to oral health and dental treatments. [Med-Science 2024; 13(4.000): 979-83]